Functionalizing graphene oxide with alkylamine by gamma-ray irradiation method - Ahmad Daud, Noraniza (MDPI, 2017)
A gamma-ray irradiation technique was used to functionalize graphene oxide (GO) with alkylamines of various alkyl chain lengths. Functionalization of the alkyl chains onto the GO was confirmed by nuclear magnetic resonance (1H NMR), Fourier transform infrared (FTIR), and X-ray diffraction (XRD). FTIR of the functionalized GO showed the appearance of significant peaks around 2960–2850 cm−1 (–CH2) which came from long alkyl chains, together with a peak around 1560–1450 cm−1, indicating the formation of C–NH–C. XRD showed an additional diffraction peak at a lower 2θ angle, indicating that the intercalation of the alkylamine was successful. The effects on the morphological and thermal properties of GO functionalized with alkyl chains of various lengths were investigated. Scanning electron microscopy (SEM) analysis showed an increase in surface roughness when the alkyl chain length was increased. The addition of alkyl chains on GO surfaces significantly improved the thermal stability of the GO, suggesting that these surfaces have great potential for use as a hydrophobic material in industry.